(untitled) - Marne, David J. (New York, N.Y., 2007)
Fully updated with all the latest rules, McGraw-Hill's National Electrical Safety Code® 2007 Handbook features: The best complete NESC® annotation currently available; A rule-by-rule overview of the entire code; Over 500 detailed illustrations and photographs; A wealth of practical examples of code applications; Concise explanations of controversial rules.
Keywords: Electric engineering,Electric engineering; Safety measures,Standards,Handbooks, manuals, etc.,Safety regulations,Handbooks, manuals, etc; United States,United States